Functionality of tRNAs encoded in a mobile genetic element from an acidophilic bacterium. Issue 4 (4th May 2018) - Alamos, Pamela; Tello, Mario; Bustamante, Paula; Gutiérrez, Fernanda; Shmaryahu, Amir; Maldonado, Juan; Levicán, Gloria; Orellana, Omar
ABSTRACT: The genome of the acidophilic, bioleaching bacterium Acidithiobacillus ferrooxidans, strain ATCC 23270, contains 95 predicted tRNA genes. Thirty-six of these genes (all 20 species) are clustered within an actively excising integrative-conjugative element (ICEA fe 1). We speculated that these tRNA genes might have a role in adapting the bacterial tRNA pool to the codon usage of ICEA fe 1 genes. To answer this question, we performed theoretical calculations of the global tRNA adaptation index to the entire A. ferrooxidans genome with and without the ICEA fe 1 encoded tRNA genes. Based on these calculations, we observed that tRNAs encoded in ICEA fe 1 negatively contribute to adapt the tRNA pool to the codon use in A. ferrooxidans. Although some of the tRNAs encoded in ICE Afe 1 are functional in aminoacylation or protein synthesis, we found that they are expressed at low levels. These findings, along with the identification of a tRNA-like RNA encoded in the same cluster, led us to speculate that tRNA genes encoded in the mobile genetic element ICEA fe 1 might have acquired mutations that would result in either inactivation or the acquisition of new functions.